Analisis Market Share Perbankan Syariah di Indonesia - Hidayat, Ahmad Rifqi; Trisanty, Aidha (At-Taqaddum, 2020)
The majority of Indonesia's population is Muslim. Ideally, the development of Islamic banking in Indonesia runs significantly, but the facts show that the market share of Islamic banks is still relatively small. This article aims to analyze the market share of Islamic banking in Indonesia. This study uses a descriptive quantitative approach. The data collection method used is the non-communication method, namely in the form of observation, literature review and experimentation through secondary data. Based on the results of the analysis and discussion, it shows that the market share of Islamic banking in Indonesia is still relatively low. The factors causing the low market share of Islamic banks and the improvement strategy are focused on three sides: Islamic banks' internal elements, aspects of government, regulators, and characteristics of society. In the future, there is a need for strategic steps from all parties to increase the market share of Islamic Banking in Indonesia.